Black saturday an essay film on the effects of the forest fire to the Bagobo-Tagabawa community in Mt. Apo - Macasio, Danielle Faye Z. (2018)
This study aimed to highlight and present the experiences of the Bagobo-Tagabawa people living in Mount Apo, and the effects of the forest fire to them through an essay film. This was achieved through an archival research to have a grasp of what were presented to the public and what they did not include, and participant-observation to get the Bagobo-Tagabawa?s perspective that will be useful in creating the film. This study was grounded by the Jacques Ranciere?s theory: The Politics of Aesthetic. This study aimed to: (1) explore the effects of the forest fire to the lives of the Bagobo-Tagabawa; (2) explore about the reactions and perceptions of the Bagobo-Tagabawaregarding the forest fire; (3) explore about the cultural implications of the forest fire to the beliefs of the Bagobo-Tagabawa; (4) present the Bagobo-Tagabawa?s experiences during the forest fire and its effects through an essay film. From the findings of the study, an essay film was conceptualized and produced showing the different perspectives relating to the forest fire.